The role of Sufism in the development of Islam among Hui Muslims in China (7th –19th centuries) - Mai, Jianjun (Universitas Islam Indonesia, 2025)
This historiographical study investigates the role of Sufism in the development and continuity of Islam among Hui Muslims in China from the 7th to the 19th centuries. Using textual and historical analysis of Chinese chronicles, travel narratives, and Islamic educational materials, the study traces the institutional and doctrinal influence of Sufi thought across major Chinese dynasties. The study demonstrates that Sufism provided essential spiritual, intellectual, and organizational frameworks that enabled Hui Muslims to maintain their religious identity despite cultural assimilation, political pressure, and periods of severe persecution. During the Yuan dynasty, Sufi practices first gained institutional footing through the establishment of lodges (zawiya) in major cities. In the Ming period, Sufism's intellectual tradition became integrated into the innovative Jingtang Jiaoyu (scripture hall education) system, which preserved Islamic knowledge through traditional Chinese educational methods. The Qing dynasty witnessed the full institutionalization of Sufism through the emergence of formal Menhuan (Sufi orders)—including Khufiyya, Jahriyya, Qadiriyya, and Kubrawiyya—that established extensive networks of spiritual authority across China. Throughout these historical periods, Sufism served as a vital channel for the development of Islam among Hui Muslims in China, strengthening their faith and preserving their religious identity by providing crucial spiritual guidance and support.